2020
DOI: 10.1021/acsomega.9b03876
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tin-Doped Titanium Oxide Nanocomposite for Efficient Photo-Anodic Water Splitting

Abstract: Herein, we report the expedient synthesis of new nanocomposite Sn0.39Ti0.61O2·TiO2 flakes using simple sol–gel and calcination methods. In order to prepare this material, first, we generated a polymeric gel using cost-effective and easily accessible precursors such as SnCl4, titanium isopropoxide, and tetrahydrofuran (THF). A small amount of triflic acid was used to initiate THF polymerization. The calcination of the resulting gel at 500 °C produced a Sn–Ti bimetallic nanocomposite. This newly synthesized Sn0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Less curvature means better efficiency of the photocatalysts. 300−302 As demonstrated in Figure 8a, Sohail et al 303 reported EIS analysis of TiO 2 doped with Sn as a Sn 0.39 Ti 0.61 O 2 • TiO 2 nanocomposite. According to Figure 8b, Ge et al 304 reported an impedance plot of TiO 2 in the rutile state.…”
Section: Recombination Pathway Of Photogenerated Species Recombinatio...mentioning
confidence: 99%
“…Less curvature means better efficiency of the photocatalysts. 300−302 As demonstrated in Figure 8a, Sohail et al 303 reported EIS analysis of TiO 2 doped with Sn as a Sn 0.39 Ti 0.61 O 2 • TiO 2 nanocomposite. According to Figure 8b, Ge et al 304 reported an impedance plot of TiO 2 in the rutile state.…”
Section: Recombination Pathway Of Photogenerated Species Recombinatio...mentioning
confidence: 99%
“…In order to prepare Fe-Ti-based nanocomposites, first we mixed ferrocene and titanium isopropoxide in THF, then and initiated THF polymerization with the addition of few drops of TFC (Scheme 3 as reported recently by our research group [47,48]. In a 50-mL round bottomed flask, ferrocene (0.00537 M, 1 g) and titanium isopropoxide (0.0075 M, 2.13 g) were dissolved in 25 mL THF at room temperature.…”
Section: Procedures For Preparation Of Fe 9 Tio 15 @Tio 2 Nanocompositementioning
confidence: 99%
“…Fe 9 TiO 15 was prepared by using 9:1 molar ratios of the precursors (0.00537 M of ferrocene and 0.000596 M of titanium isopropoxide), TiO 2 (anatase) and Fe 2 O 3 (hematite) were prepared under the similar conditions by using only titanium isopropoxide and ferrocene precursors, respectively. isopropoxide in THF, then and initiated THF polymerization with the addition of few drops of TFC (Scheme 3 as reported recently by our research group [47,48]. In a 50-mL round bottomed flask, ferrocene (0.00537 M, 1 g) and titanium isopropoxide (0.0075 M, 2.13 g) were dissolved in 25 mL THF at room temperature.…”
Section: Procedures For Preparation Of Fe 9 Tio 15 @Tio 2 Nanocompositementioning
confidence: 99%
“…Especially, nanorod arrays have received greater attention in PEC water splitting due to their advantage of highly ordered geometrical structures, which increase the charge transfer efficiency and light absorption. Numerous methods are being investigated to further improve PEC presentation of metal oxides like structural engineering, use of nanocomposites, and quantum dot sensitization . Use of nanocomposites is one of the promising methods for improving the optical, electronic, and magnetic properties of the semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methods are being investigated to further improve PEC presentation of metal oxides like structural engineering, use of nanocomposites, and quantum dot sensitization. 11 Use of nanocomposites is one of the promising methods for improving the optical, electronic, and magnetic properties of the semiconductor. In previous literature studies, zinc oxide material has been fabricated along with modification in the metal, nonmetal ion, and rare earth metals to improve its PEC activity.…”
Section: ■ Introductionmentioning
confidence: 99%